Malaysia and the Rome statute: the issue of sovereignty - Hamid, Abdul Ghafur@Khin Maung Sein (IIUM Press, International Islamic University Malaysia, 2019)
The announcement of Malaysia’s accession to the Rome Statute on March 4, 2019 was met with strong objection by the opposition and some stake holders. One of the main arguments made by those who opposed the Rome Statute was that “it will, in the end, destroy national sovereignty.” Although the argument appears to be political rhetoric, it has already injected confusion among the general public and painted a dark picture that the Rome Statute is a hegemonic law that will rob Malaysia of its sovereignty. The main purpose of the present paper, therefore, is to set the record straight and to prove the simple fact that entering into a treaty is in fact a clear exercise of a State’s sovereignty and not to lose sovereignty. First of all, the paper reappraises the concept of sovereignty: in its original form and its evolution from 16th century to 21st century, on the basis of State practice, doctrine, and judicial pronouncements. Secondly, arguments against the Rome Statute made by some powerful States are analyzed and rebutted. Thirdly, Malaysia’s situation is objectively evaluated in the light of a comparison between the Rome Statute and other onerous treaties to which Malaysia has already been a party. The paper concludes with the findings that the traditional concept of ‘absolute sovereignty’ is no longer relevant in the contemporary interdependent world, that States with their own free will as a rule restrict their sovereignty to subject themselves to international law, and that Malaysia by no means will lose its sovereignty by acceding to a treaty while most importantly the Government must first of all need to convince the people that it is a right thing to do – it is beneficial to the people of Malaysia or it can achieve the higher aim of protecting the humanity.